Scenarios of carbon dioxide emissions from aviation - Karen Mayor; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2008)
We use a model of international and domestic tourist numbers and flows to forecast tourist numbers and emissions from international tourism out to 2100. We find that between 2005 and 2100 international tourism grows by a factor of 12. Not only do people take more trips but these also increase in length. We find that the growth in tourism is mainly fuelled by an increase in trips from Asian countries. Emissions follow this growth pattern until 2060 when emissions per passenger-kilometre start to fall due to improvements in fuel efficiency. Forecasted emissions are also presented for the four SRES scenarios and maintain the same growth pattern but the levels of emissions differ substantially. We find that the forecasts are sensitive to the period to which the model is calibrated, the assumed rate of improvement in fuel efficiency and the imposed climate policy scenario.
Keywords: 330; carbon dioxide emissions; international tourism; long-term forecasting; aviation; Tourismus; Luftverkehr; Umweltbelastung; Kohlendioxid; Prognose; Welt